Experiments in macroeconomics - Duffy, John (Emerald, 2014)
Macroeconomic models and assumptions have traditionally been evaluated using non-experimental "field" data. However, in many instances the field data necessary to evaluate such models and assumptions are not available. Recently, researchers have begun to explore ways of implementing micro-founded macroeconomic models in the controlled conditions of the experimental laboratory as an alternative means of gathering the data necessary to address the empirical relevance of macroeconomic models and assumptions as well as to understand questions of equilibrium selection or policy prescriptions. This volume is the first-ever collection of laboratory studies aimed at understanding macroeconomic phenomena. The chapters, by leading researchers in the field, explore consumption behavior, expectation formation, monetary economics and central bank policy in a variety of different macroeconomic models. Readers will come away with a better understanding of how to implement macroeconomic models in the laboratory and the valuable insights that laboratory research can bring to our understanding of macroeconomics.
Keywords: Macroeconomics.; elektronické knihy; electronic books